2014
DOI: 10.1103/physrevb.90.155405
|View full text |Cite
|
Sign up to set email alerts
|

Band alignment of semiconductors from density-functional theory and many-body perturbation theory

Abstract: The band lineup, or alignment, of semiconductors is investigated via first-principles calculations based on density functional theory (DFT) and many-body perturbation theory (MBPT). Twenty-one semiconductors including C, Si, and Ge in the diamond structure, BN, AlP, AlAs, AlSb, GaP, GaAs, GaSb, InP, InAs, InSb, ZnS, ZnSe, ZnTe, CdS, CdSe, and CdTe in the zinc-blende structure, and GaN and ZnO in the wurtzite structure are considered in view of their fundamental and technological importance. Band alignments are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
285
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(324 citation statements)
references
References 114 publications
(203 reference statements)
37
285
0
2
Order By: Relevance
“…For simplicity, discussions on the bulk-Si electronic structure were not deeply done herein as they have been extensively studied in the literature [19,51,52]. In short, our results are in agreement with the available data, which yields a theoretical band gap equal to 0.63 eV.…”
Section: Electronic Structuresupporting
confidence: 86%
“…For simplicity, discussions on the bulk-Si electronic structure were not deeply done herein as they have been extensively studied in the literature [19,51,52]. In short, our results are in agreement with the available data, which yields a theoretical band gap equal to 0.63 eV.…”
Section: Electronic Structuresupporting
confidence: 86%
“…A recent comparative study has demonstrated that this approach predicts band off-sets in heterostructure interfaces rather well. [43] The CNLs have been calculated from the Kohn-Sham eigenvalues of the hybrid functional calculations by averaging the midgap energy over the first Brillouin zone and the topmost N valence bands and bottommost N conduction bands as described by Schleife et al [44] We have taken N as the number of primitive cells contained in the simulation cells employed in the DFT calculations (N = 3 for Fe 2 O 3 and N = 2 for TiO 2 ). The k-point mesh for the Brillouin zone sampling has been taken as described above for the hybrid functional calculations.…”
Section: Resultsmentioning
confidence: 99%
“…delocalization error) prevalent in approximate xc functionals [9], which further contributes to improved band gaps as well as to more accurate lattice parameters and atomization energies [10]. Hence, hybrid functionals have been widely applied to the problems of point defects in solids [11][12][13] and of band alignments at interfaces [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%